Dementia in people with severe or profound intellectual (and multiple) disabilities: Focus group research into relevance, symptoms and training needs. Issue 6 (2nd July 2021) - Dekker, Alain D.; Wissing, Maureen B. G.; Ulgiati, Aurora M.; Bijl, Bas; van Gool, Gaby; Groen, Marieke R.; Grootendorst, Esther S.; van der Wal, Ina A.; Hobbelen, Johannes S. M.; De Deyn, Peter P.; Waninge, Aly
Abstract: Background: Differentiating dementia from baseline level of functioning is difficult among people with severe/profound intellectual (and multiple) disabilities. Moreover, studies on observable dementia symptoms are scarce. This study examined (a) the relevance of dementia diagnosis, (b) observable symptoms and (c) training/information needs. Methods: Four explorative focus groups were held with care professionals and family members who have experience with people with severe/profound intellectual (and multiple) disabilities (≥40 years) and decline/dementia. Results: Thematic analysis showed that participants wanted to know about a dementia diagnosis for a better understanding and to be able to make informed choices (question 1). Using a categorisation matrix, cognitive and behavioural changes were shown to be most prominent (question 2). Participants indicated that they needed enhanced training, more knowledge development and translation, and supportive organisational choices/policies (question 3). Conclusions: Timely identifying/diagnosing dementia allows for a timely response to changing needs. This requires a better understanding of symptoms.